Efficacy and Safety of Oral Terbinafine versus Itraconazole in the Treatment of Dermatophytosis: A Randomized Clinical Trial (Journal of Armed Forces Medical College, Bangladesh, 2025)
Background: Dermatophytosis, a common fungal infection which is typically treated with a combination of systemic and topical antifungals. However, there is an increasing trend of these infections that is not responding well to conventional treatments.Objective: To assess the effectiveness and safety of two antifungal medications, oral Terbinafine and Itraconazole, in treating dermatophytic infections.Methods: This randomized clinical trial was conducted at the Department of Dermatology and Venereology, Combined Military Hospital, Ghatail and comprised of 100 patients diagnosed with Dermatophytosis. They were divided into two groups: Group A received 375 mg of Terbinafine tablets daily, while Group B was given 300 mg of Itraconazole capsules daily, in two divided dose, both for a duration of 6 weeks. Follow-ups were conducted in the 3rd and 6th weeks, during which scores for erythema, pruritus, and pigmentation were documented along with cure rate and recurrence rate. Data were analyzed by SPSS v25.Results: The mean age of the participants was 31.5±9.5 years and most were males (54%). At baseline, moderate to severe scores for erythema, pruritus, and pigmentation were noted in 49(98%), 50(100%) and 43(86%) of patients in group A and 48(96%), 49(98%) and 40(80%) of patients in group B respectively. Improvement in all the three symptoms (erythema, pruritus and pigmentation) was seen at the 6th week of treatment with no significant difference between two groups (p>0.05). From baseline to 6th week of treatment, there was no significant difference between the two groups in reducing erythema (p=0.05) and pigmentation (p=0.06). However, group A patients had a much better improvement in reducing pruritus compared to group B (p=0.006). By the 6th week of treatment, 43(87.8%) group A patients and 37(74%) group B patients were completely cured. During treatment period, a total of 28 patients reported with adverse drug reactions.Conclusion: The results of the study indicated that over a 6-week treatment period, Itraconazole and Terbinafine provided comparable outcomes.JAFMC Bangladesh, Vol 20, No 2 (December) 2024: 16-21